The existence of resolvable mendelsohn designs RMD(4, s*, v) - Qian, Yan; Du, Beiliang (Utilitas Mathematica, 2007)
The problem we study in this article is the existence of resolvable Mendelsohn design RMD(4, s*, v) which requires all blocks to be of size four except that, each parallel class should contain one block of size s, where s = 5 (when v = 1 (mod 4)), 6 (when v = 2 (mod 4)) or 7 (when v -3 (mod 4)). This article gives the spectrum of RMD(4, s*, v) for 5 ≤ s ≤ 7.